Pengaruh Kesehatan Keselamatan Kerja (K3) dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Pg. Djombang Baru) - Roudhotul Hidayati (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
The research purpose of this is to find whether there is or not the influence of work safety health and work motivation toward employees’ performance. This is an associative descriptive research using purposive sampling as the sampling technique with 123 employees. Meanwhile, the techniques of data collection used are observation, interview, questionnair and documentation. The research results show that, (1) Work safety health influences performance employees positive-partially. (2) Work motivation influences employees’ performance positive-partially. (3) Work safety health and work motivation influence employees’ performance simultaneously.